Comment on: Exact solution of theinverse-square-root potential V(r) = −α/√r - Fernández, Francisco Marcelo (2017)
We study the connection between the solutions of the Schrödinger equation with an inverse square-root potential in three and one dimension. In particular we show that an approximate analytical expression for the eigenvalues of the one-dimensional model also applies to the three-dimensional one for zero angular-momentum quantum number.